Crossbreeding indigenous East African cattle with American Angus and Red Poll - Trail, J.C.M. (Westview Press, Inc., 1984)
Presents findings of trials carried out in Uganda to characterize the indigenous Ankole, Boran and zebu cattle breeds as straightbreds for maternal traits and in crosses with exotic Angus and Red Poll males; includes data on calf crop, preweaning viability and calf weight at birth, weaning and at 2 years of age, as well as cow weight and productivity.